Task activations produce spurious but systematic inflation of task functional connectivity estimates - Cole, Michael W.; Ito, Takuya; Schultz, Douglas; Mill, Ravi; Chen, Richard; Cocuzza, Carrisa (NeuroImage (Orlando, Fla.), 2019)
Most neuroscientific studies have focused on task-evoked activations (activity amplitudes at specific brain locations), providing limited insight into the functional relationships between separate brain locations. Task-state functional connectivity (FC) – statistical association between brain activity time series during task performance – moves beyond task-evoked activations by quantifying functional interactions during tasks. However, many task-state FC studies do not remove the first-order effect of task-evoked activations prior to estimating task-state FC. It has been argued that this results in the ambiguous inference "likely active or interacting during the task", rather than the intended inference "likely interacting during the task". Utilizing a neural mass computational model, we verified that task-evoked activations substantially and inappropriately inflate task-state FC estimates, especially in functional MRI (fMRI) data. Various methods attempting to address this problem have been developed, yet the efficacies of these approaches have not been systematically assessed. We found that most standard approaches for fitting and removing mean task-evoked activations were unable to correct these inflated correlations. In contrast, methods that flexibly fit mean task-evoked response shapes effectively corrected the inflated correlations without reducing effects of interest. Results with empirical fMRI data confirmed the model's predictions, revealing activation-induced task-state FC inflation for both Pearson correlation and psychophysiological interaction (PPI) approaches. These results demonstrate that removal of mean task-evoked activations using an approach that flexibly models task-evoked response shape is an important preprocessing step for valid estimation of task-state FC. •Computational model shows task inflation of functional connectivity estimates.•Hemodynamic responses cause task activations to further inflate estimates.•Standard approaches to remove task activations leave many false positives.•Methods that flexibly fit hemodynamic response shape effectively correct inflation.•Correction of functional connectivity inflation verified with empirical fMRI data.